Agronomic performance of canola hybrids in Campos das Vertentes - MG - Vieira Pimentel, Guilherme; Alves Martins, Inara; Carvalho Santiago, Alexsandro; Costa, Natália; Nogueira Silva, Rodrigo; Guimarães Moreira, Silvino (Revista Ceres, 2024)
Canola has considerable global significance in edible oil and biodiesel production. In Brazil, canola has adapted to the temperate South region, where production is now concentrated. However, research indicates potential for growing the crop in warmer regions. This study evaluated the performance of canola hybrids under growing conditions in the Campo das Vertentes mesoregion, Minas Gerais, during the 2019 and 2021 harvests. The experiments were conducted in a randomized block 6 × 6 factorial design, with four replicates. Six canola hybrids, Hyola 433, Hyola 575 CL, Nuola 300, Hyola 571 CL, Diamond, and ALHT B4, and six sowing dates: 02/15/2019, 02/28/2019, 03/20/2019, 04/09/2019, 02/22/2021, and 03/11/2021 were tested. The plant height, total number of siliques per plant, number of grains per silique, grain yield, and canola oil yield were evaluated. The Nuola 300 and Hyola 575 CL hybrids showed superior grain and oil yields, indicating potential success in growing in the Brazilian Cerrado region. Findings indicated an optimal sowing period in the Campo das Vertentes region until March. These results stress the importance of strategically selecting hybrids and sowing timelines to maximize canola yield in the region under study.